Humanitarian Law: A Synopsis on Perspectives and Challenges in the 21st Century - Miebaka Nabiebu (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2023)
The perception of the application of international humanitarian law for both State and non-State actors in current wars is challenged by a wide range of factors related to the evolving character of warfare in the twenty-first century. The overarching goal of IHL is jeopardised by these problems, which include but are not limited to: ambiguity in the definition of violent conflict; the shifting types of actors involved; problems with asymmetric warfare; difficulties with negative reciprocity; and a limited capacity to engage with all parties to conflict. This work discusses these issues under two subtopics: transnational terrorism and the jus ad bellum, and the jus in bello and asymmetry. This work is of the opinion that formal modifications to IHL to more accurately reflect conditions will not be established anytime soon due to the sometimes-ineffective character of the international system and the lack of consensus over new legislation. This work suggests that, as a result, it is in the best interests of all parties to non-international conflicts to strive for greater adherence to the IHL standards now in place. This work further suggests that this can only be done if States acknowledge the urgent need for inclusive engagement with all non-State actors. In order to further advance the ultimate purpose of international humanitarian law—the alleviation of human suffering and the preservation of human dignity in the face of deadly armed conflict—practises of positive reciprocity must also be adhered to by all parties.